2023
DOI: 10.1093/brain/awad182
|View full text |Cite
|
Sign up to set email alerts
|

Gate control of sensory neurotransmission in peripheral ganglia by proprioceptive sensory neurons

Abstract: Melzak and Wall’s gate control theory proposed that innocuous input into the dorsal horn of the spinal cord represses pain-inducing nociceptive input. Here we show that input from proprioceptive parvalbumin-expressing sensory neurons tonically represses nociceptor activation within dorsal root ganglia. Deletion of parvalbumin-positive sensory neurons leads to enhanced nociceptor activity measured with GCaMP3, increased input into wide dynamic range neurons of the spinal cord and increased acute and spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The recent molecular and optogenetic tracing of proprioceptive primary afferents may highlight the basis for the above proposed synchronization mechanism. It was shown that input from PV-expressing proprioceptive afferents could tonically suppress nociceptor activation in the DRG [52]. The current author suggests that this finding uncovers the mechanism behind exercise-induced analgesia as was theorized in the acute compression axonopathy theory of DOMS [21].…”
Section: Peripheral Tonic Drive As Input To Theta Rhythmmentioning
confidence: 52%
See 1 more Smart Citation
“…The recent molecular and optogenetic tracing of proprioceptive primary afferents may highlight the basis for the above proposed synchronization mechanism. It was shown that input from PV-expressing proprioceptive afferents could tonically suppress nociceptor activation in the DRG [52]. The current author suggests that this finding uncovers the mechanism behind exercise-induced analgesia as was theorized in the acute compression axonopathy theory of DOMS [21].…”
Section: Peripheral Tonic Drive As Input To Theta Rhythmmentioning
confidence: 52%
“…It is important to note that this Type Ia terminal microinjury is suggested to be the Piezo2 channelopathy [9,13,40], leading to miswired proprioception [14]. Interpreting the findings of Fuller et al [52], the activation of Type II proprioceptive afferents by DOMS-inducing exercise would tonically suppress nociception in the dorsal root ganglion by GABA release from the somata of these neurons temporarily. This proprioceptive repression of nociception is the equivalent of exercise-induced analgesia; however, this would not stop the Piezo2 channelopathy-derived imbalanced leakage Ca 2+ subthreshold currents and glutamate on activated PLD-mGluR-containing glutamatergic Type Ia afferents.…”
Section: Peripheral Tonic Drive As Input To Theta Rhythmmentioning
confidence: 93%
“…Recent findings suggest that the intrinsic GABAergic system present within the DRG acts as a 'peripheral gate' within the somatosensory system (2,3,5). Importantly, direct DRG application of GABA reuptake inhibitor produces strong analgesia (2,16) while DRG injections of GABAA receptor antagonists exacerbated peripherally-induced pain (2) and reduced tonic spike filtering at the DRG in vivo (3).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is an increasing focus on the peripheral nociceptive pathways: peripheral nerves and ganglia (1). One line of enquiry illuminates peripheral somatosensory ganglia, such as the dorsal root ganglion (DRG), as an early gate within the somatosensory system (2)(3)(4)(5). Due to the pseudounipolar morphology of the DRG neurons, the action potentials, traveling from the peripheral nerve terminals to the spinal cord need to pass through the axonal bifurcation points (t-junctions) at the DRG, where there is an increasing risk of the propagation failure (2,3,(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Sensory ganglia contain the cell bodies of primary afferent neurons that transmit sensory information from the periphery into the central nervous system (Devor, 2013). These ganglia occupy a unique position, as they are the first station where sensory signals, including those of pain, are generated (Devor, 2013;Fuller et al, 2023;Raja et al, 2020). The main types of sensory ganglia are the dorsal root ganglia (DRGs), which innervate most parts of the body, including many internal organs (Vermeiren et al, 2020); and the trigeminal ganglia (TGs), which innervate the head, face and teeth (Chiang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%